Use of Sulfuric Acid-Impregnated Biochar Catalyst in Making of Biodiesel From Waste Cooking Oil Via Leaching Method - Sofyan, Muhammad Ihsan; Mailani, Putri Julpa; Setyawati, Avi Waras; Sulistia, Susi; Suciati, Fuzi; Hauli, Latifah; Putri, Reza Audina; Ndruru, Sun Theo C. L.; Mawarni, Rista Siti; Meliana, Yenny; Nurhayati, Nurhayati; Joelianingsih, Joelianingsih (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
The biodiesel synthesis of waste cooking oil (WCO) over a impregnated biochar catalyst was systematically studied. This research aimed to prepare Biochar-based material that comes from coconut coir, activate it, and apply it as a catalyst to the esterification reaction of high-FFA waste cooking oil. Activation of the catalyst was done by impregnation H2SO4 solution in Biochar. The obtained catalyst was characterized by FTIR, XRF, XRD, surface area analyzer, and SEM-EDS. The esterification process was conducted by varying the catalyst weight (5, 7, and 10 wt%) and the reaction temperature (55 and 60 °C). The obtained liquid yields were characterized by GC-MS. The study found that the esterification process worked best with 10 wt% catalysts, a 1:76 mole ratio of oil to alcohol, and a reaction temperature of 60 °C. The waste cooking oil was successfully converted into biodiesel, reaching 84.50% of yield and 77.30% of purity (methyl ester content). Meanwhile, testing using national biodiesel standards with parameter limits of density, viscosity, iodine number, and acid number shows results that meet the requirements. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).